Variabilidade espacial e estimativa da condutividade hidráulica e caracterização física-hídrica de uma microbacia hidrográfica rural - Dalbianco, Leandro (2009)
The soil management systems involve changes in soil physico-hydrical properties. The objective of this study was (i) characterize the soil physico-hydrical properties in the layer 0-5 cm for different soil management systems in the Cândido Brum watershed, (ii) build a map with the spatial variability of soil saturated hydraulic conductivity (Ks), (iii) estimate the Ks from other soil physico-hydrical properties and (iv) test the reliability of others pedotransfer functions for Ks found in the literature. The study was conducted in the watershed Cândido Brum, Brazil, which predominate the soil management systems native pasture, native forest, conventional tillage, minimum tillage and no-tillage. Orthogonal contrasts were performed between groups of soil management systems, which compared the effect of soil cultivation, the type of vegetation and bovine trampling, conservation practice and permanent soil cover. Determinations of soil bulk density, porosity, size particles, organic carbon, degree of flocculation, aggregate stability, Ks, air permeability, retention and availability of water and shear stress of the soil were made. Besides being used for the comparison of management systems, the water-physical properties used as input variables for the development of pedotransfer functions for Ks, which used the stepwise method in the selection of variables, and to test the reliability of pedotransfer functions found in the literature. The map of spatial variability of Ks was constructed from data interpolation using kriging. The soils of the watershed under crops had degraded structure, with low organic matter and low aggregates stability. Soil with native pasture had reduced the macroporosity, the Ks and air permeability in relation to other soil management systems. Conservation practices were effective in increasing the retention and vailability of soil water in relation to conventional tillage. The variables that represent the structure of the soil were more accurate in estimating the Ks that the size particle variables. The pedotransfer functions found in the literature, usually developed for soils of temperate climate, were not reliable in the estimation of Ks of soils watershed. The range of spatial dependence of the values of Ks was 141 m. The map of spatial variability allowed the visualization of areas that need management practices and conservation of soil and water.